(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate factors associated with the intention to reuse outpatient clinic services at Nguyen Tri Phuong Hospital. Methods: A cross-sectional descriptive study was conducted among 160 outpatients and their accompanying relatives aged 18 years or older who had visited the hospital within the previous six months. Data were collected using a structured questionnaire based on the SERVQUAL model with a five-point Likert scale. Scale reliability, descriptive statistics, and Pearson correlation analyses were performed using SPSS 20.0 software. Results: All measurement scales demonstrated acceptable to excellent reliability (Cronbach’s Alpha ranging from 0,65 to 0,96). Mean scores of SERVQUAL dimensions ranged from 3,73 to 4,20. Assurance and Empathy received the highest ratings, whereas Tangibility and Responsiveness were rated relatively lower. Overall patient satisfaction was 3,86 ± 0,38 points, and the intention to reuse services was 3,74 ± 0,60 points. Service quality dimensions showed significant positive correlations with satisfaction and revisit intention (p < 0,001). Notably, satisfaction was strongly correlated with revisit intention (r = 0,86). Health insurance coverage was the primary factor motivating patients to return, while long waiting times were the main source of dissatisfaction. Conclusion: Outpatients at Nguyen Tri Phuong Hospital reported moderate to good levels of satisfaction and intention to reuse services. Maintaining professional competence and positive staff attitudes, along with improving physical facilities and reducing waiting times, are key strategies to enhance patient experience and encourage service reuse.